1
$\begingroup$

I found a similar problem on one of my problem sets and am struggling with how to approach the problem.

The problem is as follows: $$ \text{Evaluate} \sum _{k=1}^{n}\:P(n, k-1)P(n-1,n-k). $$

The function $P(n, r)$ represents the number of permutations of length $r$ you can form from $n$ total objects.

Using a Computer Solver (Sympy), I know that the answer is $(2^{n}-1)(n-1)!$. However, I am not sure how to get there. I would appreciate any insights into how to approach this problem and/or a walkthrough on how to get the solution.

$\endgroup$
4
  • 1
    $\begingroup$ Multiplying both sides by $n$ you get $$(2^n-1)n!=\sum_{1}^n P(n,k-1)P(n,n-(k+1))=\sum_{j=0}^{n-1} P(n,j)P(n,n-j).$$ That seems simpler. $\endgroup$ Commented Mar 15, 2022 at 19:21
  • $\begingroup$ Often, you can do these things by counting a set in two different ways. The left side of my simpler equation counts pairs a permutation $\sigma$ of $\{1,2,3,\dots,n\}$ and a non-empty subset $S$ of $\{1,2,3,\dots,n\}.$ There might be a way to compute a function $f(\sigma,S)$ so that the count of pairs $(\sigma,S)$ with $f(\sigma,S)=j$ is $P(n,j)P(n,n-j).$ But I’m not seeing it off the top of my head right now. $\endgroup$ Commented Mar 15, 2022 at 19:28
  • $\begingroup$ Sorry, in my first comment, it should be $$\sum P(n,k-1)P(n,n-(k-1)).$$ But the final step is right. $\endgroup$ Commented Mar 15, 2022 at 19:31
  • $\begingroup$ Anyway, other than the computer solver, what have you tried? Do you know the closed formula for $P(n,r)?$ Do you know binomials? $\endgroup$ Commented Mar 15, 2022 at 19:34

2 Answers 2

1
$\begingroup$

$$\sum_{k=1}^nP(n,k-1)P(n-1,n-k)=\sum_{k=1}^n \frac{n!}{(n-k+1)!}\cdot\frac{(n-1)!}{(k-1)!}\\=\sum_{k=0}^{n-1} \frac{n!}{(n-k)!}\cdot\frac{(n-1)!}{k!}=(n-1)!\sum_{k=0}^{n-1} \cdot\frac{n!}{k!(n-k)!} \\=(n-1)!\sum_{k=0}^{n-1} {n\choose k}=(n-1)!\,(2^{n}-1)$$

$\endgroup$
0
$\begingroup$

Just write

$$P(n,r) = \binom nr \cdot r!$$

and note that $\sum_{k=0}^n\binom nk =2^n$.

So, you get

\begin{eqnarray}\sum_{k=1}^{n}\:P(n, k-1)P(n-1,n-k) & = & \sum_{k=1}^{n}\binom n{k-1}(k-1)!\binom{n-1}{n-k}(n-k)! \\ & = & \sum_{k=1}^{n}\frac{n!(n-1)!}{(n-(k-1))!(n-1-(n-k))!} \\ & = & (n-1)!\sum_{k=1}^{n}\binom n{k-1} \\ & = & (n-1)!(2^n-1) \end{eqnarray}

$\endgroup$

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .